2022
DOI: 10.3390/vaccines10030416
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ethical Leadership, Commitment and Healthy/Safe Workplace Practices toward Employee Attitude to COVID-19 Vaccination/Implantation in the Banking Sector in Lebanon

Abstract: This study investigates the effect of ethical leadership, commitment and healthy/safe workplace practices toward employee COVID-19 vaccination. In addition, this study examines the perception of employees from technological intrusive vaccination of chips or quantum dot. In our research, we adopted the social exchange theory as its theoretical framework. Moreover, an online questionnaire was distributed to employees working in the banking sector in Lebanon during the COVID-19 pandemic. In total, 244 bankers com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(19 reference statements)
0
6
0
Order By: Relevance
“… 52 Moreover, other studies assessed the negative perceptions of both the disease and the vaccine among employees and found that there is a positive relationship between ethical leadership, commitment, and safety influencing employees to accept COVID-19 vaccination. 53 …”
Section: Resultsmentioning
confidence: 99%
“… 52 Moreover, other studies assessed the negative perceptions of both the disease and the vaccine among employees and found that there is a positive relationship between ethical leadership, commitment, and safety influencing employees to accept COVID-19 vaccination. 53 …”
Section: Resultsmentioning
confidence: 99%
“… 38 40 Later on and with the development of vaccines against SARS-CoV-2, a new publication from the LAU concluded that organizations should influence leaders to enhance proper behaviors and attitudes to create a healthy, safe, and ethical culture that consequently increases employees’ commitment to COVID-19 vaccination. 41 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, few studies have discussed the impact of COVID-19 on employees' psychological health and aimed at exploring the relationship between organizational learning and work engagement amid the COVID-19 pandemic through testing the mediating role of employee resilience and psychological empowerment on this relationship [54]. Moreover, other studies assessed the negative perceptions of both the disease and the vaccine among employees and found that there is a positive relationship between ethical leadership, commitment, and safety in uencing employees to accept COVID-19 vaccination [55].…”
Section: Study Objectives and Endpointsmentioning
confidence: 99%